(3bUjOI GdMeGeI hGdUbQs - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s ((3eMeO Jbj Hf YHOGddg s)
(3ChdgG (B:s
(3SQJ SMQkG Sdei hSQ Hj GdeSQi aRGQJ, aRGd Gdge Yf cHOj MQkG s
(3BNQgG (B:s
(3Ydjce UdGI Gddg jG Bd CMeO Ydjce UdGI cd HGQbI JJQi s
(3fXegG aj GdeYLRI GdJj UOQJ ef Ydj Hf CHj WGdH aj GdMeGeI hGdUbQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B112 s
Keywords: (3GdCOHs